2020
DOI: 10.1038/s41598-020-72131-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparing preference of ankle–foot stiffness in below-knee amputees and prosthetists

Abstract: When fitting prosthetic feet, prosthetists fuse information from their visual assessment of patient gait with the patient’s communicated perceptions and preferences. In this study, we sought to simultaneously and independently assess patient and prosthetist preference for prosthetic foot stiffness using a custom variable-stiffness prosthesis. In the first part of the experiment, seven subjects with below-knee amputation walked on the variable-stiffness prosthetic foot set to a randomized stiffness, while sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
(31 reference statements)
0
25
0
Order By: Relevance
“…Machine testing combined with a variable stiffness unit can be beneficial for researchers and prosthetic foot designers to better understand prosthetic foot properties and possibly the specific user preferences. Shepherd and Rouse showed the interaction between the CPO and the user when comparing ankle-foot stiffness preference [31]. We foresee the potential of these types of machine testing results to be optimized for user-specific input profiles.…”
Section: Discussionmentioning
confidence: 98%
“…Machine testing combined with a variable stiffness unit can be beneficial for researchers and prosthetic foot designers to better understand prosthetic foot properties and possibly the specific user preferences. Shepherd and Rouse showed the interaction between the CPO and the user when comparing ankle-foot stiffness preference [31]. We foresee the potential of these types of machine testing results to be optimized for user-specific input profiles.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, it is likely that there are users for which the population average impedance parameters are not optimal. A study investigating users' preferred stiffness in ankle prostheses showed that the preferred joint stiffness varies by user [43], which is likely true for knee-ankle prosthesis users as well. While one of the major advantages of HKIC is that it required no manual tuning, it could be limited by the lack of an ability to customize to an individual's preferred behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The dial could be freely rotated beyond the minimum and maximum of VSPA stiffness; however, the VSPA Foot saturated at these extrema, such that any supramaximal changes to the dial were ignored by the controller. This method of adjustment converges faster to the user's preference than the two-alternative forced choice methods we have previously implemented [45,49], and produces slower and more predictable (and thus safer) stride-to-stride adjustment of mechanics. Although subjects were free to rotate the dial throughout the gait cycle, stiffness was only actively adjusted, to match the value indicated by the dial's position, during the swing phase of gait.…”
Section: Preference Identificationmentioning
confidence: 99%
“…The second key hurdle is that the field's understanding of preference is not yet sufficient to enable robust interpretation by researchers, payers, and providers. For instance, it is not known how preferred device parameters relate to typical clinical metrics of performance, such as the 10 Meter Walk test (10MWT), or whether users prefer parameters that are "good for them" long term [45]. If user-preferred parameters align with these more wellknown metrics, providers may place more trust in the feedback they receive from patients.…”
Section: Introductionmentioning
confidence: 99%